The role of the Administrative Control Authority in reducing economic crime in Libya (A case study on the authority’s branches in Benghazi, Ajdabiya and Tobruk) (Journal of Human Sciences, 2022)
This study aimed to identify the role of the Administrative Control Authority in reducing economic crime in Libya with a review of the components of the effective supervisory system, identifying the supervisory activities that reduce economic crime, and the responsibility of the Administrative Control Authority in discovering corruption. The researchers used the descriptive approach in conducting the study By collecting data from its primary and secondary sources, a questionnaire was prepared specifically for this purpose, and distributed to the study population of (42) single employees, department managers and heads of departments from the Administrative Control Authority in Libya. And the use of one of the statistical methods, which is the descriptive analytical method, to analyze data and information. The study reached a set of results, the most important of which were: The study indicates that the respondents’ expectations were not optimistic about the prevailing political situation in the country, which contributed to the high incidence of economic crimes. The study proved the validity of the hypothesis of a relationship between Administrative Control Authority procedures and low rates of economic crime.        The study concluded with a set of recommendations, the most important of which were: Paying attention to the personal characteristics of the employees in the Authority, because of their importance to the success of the career path. Thus, the Authority can provide a full explanation of the jobs in them, and the conditions that must be met by the occupants of these jobs, and thus it can reach the compatibility between personal characteristics and job characteristics, thus bringing the right person to the right place. The current study recommends that the authority pay attention to the expectations of its employees, their ambitions and the possibility of achieving them, and encourage cooperation between the branches of the Administrative Control Authority.